PENDEKATAN PEMIKIRAN AGAMA: BAYANI, IRFANI, DAN BURHANI - Yaqdzon Fariduzaman; Kahla Assyifa; Maftuh Ajmain (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to analyze religious thought approaches in Islam through three main epistemological frameworks: Bayani, Irfani, and Burhani. These approaches represent different ways of understanding truth, namely through revealed texts, spiritual experience, and rational reasoning. The method used in this study is library research with a descriptive-qualitative approach, examining various literature related to Islamic epistemology and philosophy of religion. The results show that the Bayani approach plays a role in preserving the authenticity of religious teachings through textual authority, the Irfani approach provides spiritual depth through inner experience, while the Burhani approach offers a rational dimension capable of addressing modern challenges. The integration of these three approaches is essential to produce a comprehensive, balanced, and contextual understanding of religion. Therefore, this study is expected to contribute to the development of Islamic studies methodology that is more open, critical, and relevant to contemporary developments.